Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Balai Besar Pelaksanaan Jalan Nasional VI Jakarta - Mitri Nelsi; Ali Zaenal Abidin; Dian Rostikawati (Jurnal Tadbir Peradaban, 2021)
This study aims to determine the effect of motivation and work environment on employee performance at the Great Hall for the Implementation of National Road VI Jakarta. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study motivation significantly influence employee performance by 48.8%, hypothesis testing obtained t count > t table or (7.439 > 2.002). The work environment has a significant effect on employee performance by 44.9%, hypothesis testing is obtained t count > t table or (6.873 > 2.002). Motivation and work environment simultaneously have a significant effect on employee performance with the regression equation Y = 7,469 + 0,416X1 + 0,413X2 and the contribution of the influence is 62,7%.